EVELYN: war boat / M.Danial Haikal Masri - Masri, M.Danial Haikal (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
EVELYN is a war boat specially designed for the purpose of carrying out activities that invite danger to the country that occur on or in the water whether in a river, lake, or sea. It has the latest features such as radar, GPS & advanced computer system to monitor the condition of the boat & during operation. The boat uses a high-powered engine that allows it to move faster & allows any operation to run smoothly. Its various functions coupled with advanced features make this boat a practical boat and suitable for use in any operation or situation. Indeed, EVELYN is the long-awaited war boat by those who need a water vehicle that meets their needs.